Inductive Load Analysis of a 15 HP Induction Motor A Case Study on Energy Efficiency and Power Factor Correction in a Palm Oleo Processing Plant - Agus Supriyadi; Rahmaniar Rahmaniar; Zuraidah Tharo (Sean Institute, 2026)
This study aims to analyze the impact of inductive loads on the performance of a three-phase power system using a 15 HP induction motor and to evaluate the effectiveness of power factor correction in improving energy efficiency. The research employs a mathematical analysis approach based on a three-phase power system model by considering active power, reactive power, apparent power, current, and power losses under load variations of 50%, 75%, and 100%. The results indicate that the power factor decreases under partial-load conditions, reaching as low as 0.66, which leads to higher current demand and increased power losses. Following power factor correction using a 5 kVAR capacitor bank, the power factor improved to 0.95. This improvement resulted in approximately a 14% reduction in system current and a decrease in power losses of 192 W. Furthermore, the reduction in reactive power consumption lowered the kVARh-to-kWh ratio, thereby eliminating the potential utility penalty charges associated with excessive reactive energy usage. Overall, the findings demonstrate that power factor correction is an effective solution for enhancing energy efficiency, improving power system performance, and reducing operational costs in industrial systems driven by induction motors.